Click chemistry approaches for developing carbonic anhydrase inhibitors and their applications - Andrea Angeli; Claudiu T. Supuran (Taylor & Francis Group, 2023)
Click chemistry reactions constitute an important and relatively new approach in the medicinal chemistry toolbox and offer substantial advantages to medicinal chemists in terms of overcoming the limitations of facile chemical synthesis, increased throughput, yields and improved quality of compound libraries. Over the last two decades, click chemistry has been widely used in different aspects of carbonic anhydrase (CA, EC 4.2.1.1) modulators drug design. This review provides an overview of the general principles and applications of click chemistry in CA-related research, including the design of selective CA inhibitors (CAIs), their applications against several diseases such as innovative anticancer and anti-infective agents, fluorescent and radiopharmaceutical probes as new theranostic agents, as well as their application in protein labelling.